Messianic movements and the sacralization of the territory - Pace, Vincenzo (REVER: Revista de Estudos da Religião, 2020)
This article focuses on contemporary Messianic Judaism. The author deals particularly with the Chabad and Gush Emunim movements, which have established many settlements in the West Bank, Sinai Peninsula, Gaza Strip, and Golan Heights. These settlements not only satisfy a vital need for living space but are also the expression of strong Messianic tension. This tension produces a mundus imaginalis (Corbin), the boundaries of which come between heaven and earth, between the biblical contours of the Promised Land and the harsh reality of a territory marked by war. The object of analysis is the toponymic politics developed by these Messianic movements in order to sacralize the territory in view of the coming of the Messiah.